Multiscale engineered artificial compact bone via bidirectional freeze-driven lamellated organization of mineralized collagen microfibrils - Lingwenyao Kong; Yonggang Zhao; Yang Xiong; Junlin Chen; Shuo Wang; Ziming Yan; Huibin Shi; Zhanli Liu; Xiumei Wang (Bioactive Materials, 2024)
Bone, renowned for its elegant hierarchical structure and unique mechanical properties, serves as a constant source of inspiration for the development of synthetic materials. However, achieving accurate replication of bone features in artificial materials with remarkable structural and mechanical similarity remains a significant challenge. In this study, we employed a cascade of continuous fabrication processes, including biomimetic mineralization of collagen, bidirectional freeze-casting, and pressure-driven fusion, to successfully fabricate a macroscopic bulk material known as artificial compact bone (ACB). The ACB material closely replicates the composition, hierarchical structures, and mechanical properties of natural bone. It demonstrates a lamellated alignment of mineralized collagen (MC) microfibrils, similar to those found in natural bone. Moreover, the ACB exhibits a similar high mineral content (70.9 %) and density (2.2 g/cm3) as natural cortical bone, leading to exceptional mechanical properties such as high stiffness, hardness, and flexural strength that are comparable to those of natural bone. Importantly, the ACB also demonstrates excellent mechanical properties in wet, outstanding biocompatibility, and osteogenic properties in vivo, rendering it suitable for a broad spectrum of biomedical applications, including orthopedic, stomatological, and craniofacial surgeries.